Utilizing English Songs to Enhance Students’ Motivation in Learning English - Maromon, Maria M. (Journal of Language, Education, Literature, and Culture, 2025)
This study, entitled "Utilizing English Songs to Enhance Students’ Motivation in Learning English." Consequently, the research is framed around the central question: "What is the most effective time to employ songs in teaching English to motivate students?" The aim is to determine the best time to employ songs in teaching English to motivate students: at the beginning, midway, or end of the lesson. It is hoped that once teachers know the best time to play a song, they will implement it to encourage and motivate students to learn English better. The method used was a quasi-experiment to measure students' scientific attitudes and learning motivation. In this design, one class was given the treatment, and each meeting was assessed using an observation sheet to measure scientific attitudes and a student learning motivation questionnaire. The results of the study found that the best time to use songs to motivate students to learn English is midway through the lesson. Playing songs at this time is believed to attract students' attention throughout the lesson, thereby maintaining their motivation. Therefore, teachers are expected to pay attention to creating a pleasant learning atmosphere by using songs midway through the lesson.